Dance in a Haunted Space: Genre, Form, and the Middle English Carol. (May 2015) - Chaganti, Seeta
Abstract : The premodern ghost in danced motion offers a visual, kinetic, and material language to express the Middle Ages' perception of genre as a spatial phenomenon. This essay makes this case by drawing on the contemporary discourse of virtuality to consider the medieval ghost's uses of space. The essay begins by positing the dancing ghost as emblematic of the carol as a particular genre. It then employs the ghost to clarify the carol genre's relationship to its form. Ultimately, the essay suggests that the dancing ghost lends explicating shape to the broader concept of generic categorization.